Social religious solidarity of East Nusa Tenggara Muslim minorities in the blessing movement program at the Cahaya Hijrah Foundation - Effendi, Muhamad Ridwan; Wajdi, Firdaus; Rasidin, Bagus (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2023)
This study aims to describe the blessing movement among Muslim minorities in East Nusa Tenggara by the Cahaya Hijrah Foundation to strengthen religious social solidarity between Muslim and non-Muslim communities. The descriptive qualitative approach was used to research subjects, namely Yayasan Cahaya Hijrah and minority Muslim communities in the Kupang Area. Based on the analysis of Emile Durkheim's social solidarity theory, it is stated that first, the blessing movement program is considered to have an impact on strengthening the solidarity of Muslim and non-Muslim communities in Kupang, especially in the aspect of emotional-spiritual experience, second, the form of religious solidarity in the blessing movement carried out by the Cahaya Hijrah Foundation is seen in cooperation activities for the construction of places of worship, empowerment of religious activities, and the implementation of education